Monitoring the Stability of Oxygen Flow Analyzer on Oxygen Station in the Hospital - Rosida, Nur Khabibatul; Rahmawati, Triana; Wisana, I Dewa Gede Hari; Nosike, Maduka (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
In addition to benefits, oxygen therapy also has certain dangers and side effects. Hence, oxygen therapy must be given at the proper dose by monitoring the patient regularly and adjusting the oxygen flowmeter. The accuracy of flowmeter under standard conditions is guaranteed by manufacturer. Through time and use, the precision may change and the flow accuracy given in a hospital setting may different from the original value. Related to this matter, current research was carried out aiming to conduct further research on oxygen flow analyzer which focused on discussing the accuracy and stability of the oxygen flow sensor against the gold standard. The contribution of this study is to increase the range of oxygen flowrate measurement to 15 liters per minute (LPM). Furthermore, this research used Arduino Mega, while the gas flow sensor used was legris flow sensor. The measurement results were further displayed on TFT LCD equipped with SD Card data storage. The gas flowrate was regulated using a flowmeter (GEA). Meanwhile the comparison tools used Oxygen Analyzer and 1 m3 oxygen gas cylinder. At the testing stage, the sensor reading value on the module that appeared on the TFT LCD was compared with the resultsf a comparison tool with a measurement range of 1 LPM to 15 LPM 6 times at each point. The conclusion from these results is that the calibrator module has a relative error that is still within the allowable tolerance limit of ±10%.